Human Capital And The Use Of Information Technology To Enhance Sustainable Competitive Advantages: (Case study on Sharia Banking) - Hidayah, Nurul; Badawi, Ahmad; Nugroho, Lucky; Moetopo, (Archives of Business Research, 2020)
This study aims to determine the effect of human capital and the use of information technology on the competitive advantage of Sharia banking. The study takes an analysis unit of Indonesia Sharia banking. The type of data used is primary data using a questionnaire which sampling used is a stratified random sampling model where respondents in this study consist of leaders and employees in Sharia banking. This research uses desciptive qualitative approach. Data analysis used PLS consisting of Outer Model test (Validity and Reliability) and Inner Model test (coefficient of determination and T test). The results show that human capital has no significant effect and the use of information technology has a significant effect on the sustainable competitive advantage of Sharia Banking.